INVESTIGATION OF JOB SATISFACTION LEVELS OF COACHES IN ELAZIĞ - Şenbakar, Kubilay (İbrahim ERDEMİR, 2021)
With this study, it was aimed to determine the job satisfaction levels of coaches. The universe of the research is composed of the trainers of the faculty of sports sciences in the Eastern Anatolia region. The sample consists of 87 trainers chosen randomly among these trainers. In the second part of the personal information form (gender, marital status, age) to determine the demographic information of the Football coaches participating in the study, the Minnesota Job Satisfaction Scale is a five-point Likert-type scale scored between 1-5. In Olcek scoring, I am not satisfied at all; 1 point, I'm not satisfied; 2 points, I'm indecisive; 3 points, Satisfied; 4 points, I am very satisfied; It is evaluated as 5 points. There is no reverse scored item in the scale. The Minnesota Job Satisfaction Scale consists of 20 items with features that determine the internal, external, and general satisfaction level (Yelboğa 2007). SPSS 22.0 statistics program was used to analyze the data in the study and calculate the results. As a result of the analyzes, it was found that there was a significant difference in the sub-dimension of general satisfaction in the gender variable, in the internal satisfaction and external satisfaction in the marital variable, and in the internal, external and general satisfaction in the age analysis. In our study, it has been determined that the values are above average. As a result; Significant differences were found in the sub-dimensions of the football coaches' job satisfaction scale as a result of the analysis performed in the variables of gender, marital status and age. It has been observed that female trainers have higher attitudes towards their job than male trainers. It has been observed that single coaches are more committed to their work than those who are married, and it has been found that coaches aged 31-35 are more committed to their work than other coaches

Bu calışma ile antrenörlerinin iş doyumu duzeylerinin belirlenmesi amaclanmıştır. Araştırmanın evreninini 2019 yılında Elazığ ilinde bulunan antrenörler oluşturmaktadır. Orneklemi ise bu Antrenörlerin içinden rastgele yöntemle seçilen 87 antrenör oluşmaktadır. Araştırmaya katılan Futbol antrenörlerinin demografik bilgilerini belirlemek amacıyla kişisel bilgi formu (Cinsiyet, medeni durum, Yaş) ikinci bolumde ise Minnesota İş Doyum Olceği 1-5 arasında puanlanan beşli likert tipi bir olcektir. Ölcekte ters puanlanan madde bulunmamaktadır. Minnesota İş Doyum Olceği icsel, dışsal ve genel doyum duzeyini belirleyici ozelliklere sahip 20 maddeden oluşmuştur (Yelboğa 2007). Çalışmadaki verilerin analizi ve bulunan sonucların hesaplanmasında SPSS 22,0 istatistik programı kullanılmıştır. Yapılan analizler soncunda cinsiyet değişkeninde genel doyumda alt boyutunda, Medeni dutum değişkeninde içsel doyum ve dışsal doyum, yaş analizinde ise içsel, dışsal ve genel doyumda anlamlı farklılık olduğu saptanmıştır. Yaptığımız çalışmada değerlerin ortalamanın üstünde olduğu tespit edilmiştir. Sonuç olarak; Futbol antrenörlerinin İş doyumu ölçeğinin alt boyutlarında cinsiyet, medeni durum ve yaş değişkeninde yapılan analizler sonucunda anlamlı farklılıkların olduğu saptanmıştır. Kadın antrenörlerinin erkek antrenörlerine göre işlerine olan tutumları daha yüksek olduğu görülmüştür. Bekar olan antrenörlerinin evli olanlara göre daha çok işlerine bağlı olduğu görülmüş ve 31-35 yaşındaki antrenörlerinin diğer antrenörlerine göre işlerine daha çok bağlı oldukları saptanmıştır.
Elazığ İlindeki Antrenörlerin İş Doyum Düzeylerinin İncelenmesi
Keywords: Sports Medicine; Spor Hekimliği